2020
DOI: 10.1177/0002764220956688
|View full text |Cite
|
Sign up to set email alerts
|

Nonjudicial Influence on Family Violence Court Cases

Abstract: Family courts have rarely considered how their decisions are perpetuating domestic violence and child abuse in the many cases where custody disputes are before them. Rather than judges playing King Solomon themselves, they frequently leave the decision making to mental health professionals and lawyers whose credentials rarely include an understanding of what is needed to recognize, stop current abuse and prevent future violence. This article employs a literature review to examine the consequences of this decis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
(67 reference statements)
0
3
0
Order By: Relevance
“…This is even more likely to occur if the abusive father cross-claims that the mother is alienating him from the child. For more examples and an overview of nonjudicial influences in family violence cases, readers are encouraged to review Walker and Diaz (2022). The American Psychological Association (APA) has recently cited the disparities in health care for all marginalized people, especially women from lower economic communities.…”
Section: Cultural Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…This is even more likely to occur if the abusive father cross-claims that the mother is alienating him from the child. For more examples and an overview of nonjudicial influences in family violence cases, readers are encouraged to review Walker and Diaz (2022). The American Psychological Association (APA) has recently cited the disparities in health care for all marginalized people, especially women from lower economic communities.…”
Section: Cultural Issuesmentioning
confidence: 99%
“…The second portion utilizes a weighted system assessing risk factors associated with intimate partner homicide (Campbell, 2003). Walker and Diaz (2022) found that in a sample of BW who killed their abuser in self-defense, a majority of the women's DA scores suggested their level of perceived danger fell within the Extreme range prior to the incident.…”
Section: Structured Clinical Interviews and Surveysmentioning
confidence: 99%
“…The current study reports on the impacts of shared parenting arrangements on young children (0-4 years) when domestic violence has occurred. Domestic violence, also known as intimate partner violence (IPV), is gaining acceptance across many jurisdictions as more than just physical violence (Elizabeth, 2015), for example, in New Zealand (Elizabeth, 2017), Australia (Douglas, 2018), UK (Barnett, 2015), Hungary (Galátai et al, 2019), Canada (Fotheringham et al, 2013), and in the United States (Gutowski & Goodman, 2020;Walker, 2020). Domestic violence is defined in research literature as both physical violence and coercive control (Treloar & Boyd, 2014;Elizabeth, 2015), and is understood this way for our study.…”
Section: Introductionmentioning
confidence: 99%